Transhepatic Therapies for Metastatic Uveal Melanoma - Eschelman, David J.; Gonsalves, Carin F.; Sato, Takami (Seminars in Interventional Radiology, 2013)
Despite successful treatment of the primary tumor, uveal melanoma has a propensity to metastasize to the liver. Prognosis is poor due to the very aggressive nature of these tumors. Because systemic therapies are relatively ineffective and patient survival correlates to disease control in the liver, locoregional therapies provide a means of prolonging survival. We review various techniques including chemoembolization, immunoembolization, radioembolization, arterial fotemustine infusion, and hepatic perfusion for the treatment of liver metastases from uveal melanoma.
Keywords: uveal melanoma; liver metastases; chemoembolization; immunoembolization; radioembolization